Cumulation of Marriage Itsbat and Talak Divorce Lawsuits (Case Study Decision No. 5361/Pdt.G/2022/PA.Badg.) - Perwitiningsih Perwitiningsih (Kosmik Hukum, 2024)
The civil law that applies in Indonesia does not standardize provisions regarding cumulative lawsuits, especially cumulative lawsuits on marriage itsbat and talak divorce. In Decision No. 5361/Pdt.G/2022/PA.Badg., there is a marriage itsbat and talak application. This normative research that aims to analyze how the provisions in Indonesian legislation regulate the accumulation of itsbat of marriage and talak lawsuit and to analyze the judge’s decision to grant the application for itsbat of marriage, especially unregistered marriages for pregnant women and talak for pregnant woman. This research concludes that the provisions in article 7, paragraph (3) letter (a) KHI can be used as a legal basis for cumulative lawsuits of marriage itsbat and divorce. According to Article 53 KHI, marriages for pregnant women can still held because they have fulfilled the legal requirements for marriage and no statutory provisions have been violated. Article 19 letter (f) Government Regulation Number 9 of 1975 concerning Implementation of Law Number 1 of 1974 concerning jo. Article 116 letter (f) KHI can be taken into consideration by the Panel of Judges when granting the petitioner’s talak divorce application.Keywords: cumulative lawsuit, marriage itsbat, talak divorce